Epigallocatechin Gallate-Mediated Cell Death Is Triggered by Accumulation of Reactive Oxygen Species Induced via the Cpx Two-Component System in Escherichia coli - Nie, Tao; Zhang, Chenlu; Huang, Antian; Li, Ping (Frontiers in Microbiology, 2018)
The high antimicrobial activity of epigallocatechin gallate (EGCG), the most bioactive component of tea polyphenol with a number of health benefits, is well known. However, little is known about the mechanism involved. Here, we discovered the relationship between reactive oxygen species (ROS), the Cpx system, and EGCG-mediated cell death. We first found an increase in ampicillin resistance as well as the transcription level of a LD-transpeptidase (LD-TPase) involved in cell wall synthesis; ycbB transcription was upregulated whereas that of another LD-TPase, ynhG, appeared to be constant after a short exposure of Escherichia coli to sub-inhibitory doses of EGCG. Additionally, the transcription level of cpxP, a downstream gene belonging to the Cpx regulon, was positively correlated with the concentration of EGCG, and significant upregulation was detected when cells were treated with high doses of EGCG. Through analysis of a cpxR deletion strain (ΔcpxR), we identified a constant ROS level and a notable increase in the survival rate of ΔcpxR, while the ROS level increased and the survival rate decreased remarkably in the wild-type strain. Furthermore, thiourea, which is an antioxidant, reduced the ROS level and antimicrobial activity of EGCG. Taken together, these results suggest that EGCG induces ROS formation by activating the Cpx system and mediates cell death.